2014
DOI: 10.3109/10408363.2014.944299
|View full text |Cite
|
Sign up to set email alerts
|

The decalog of long non-coding RNA involvement in cancer diagnosis and monitoring

Abstract: Long non-coding RNAs (lncRNAs) are transcripts without protein-coding capacity; initially regarded as "transcriptional noise", lately they have emerged as essential factors in both cell biology and mechanisms of disease. In this article, we present basic knowledge of lncRNA molecular mechanisms, associated physiological processes and cancer association, as well as their diagnostic and therapeutic value in the form of a decalog: (1) Non-coding RNAs (ncRNAs) are transcripts without protein-coding capacity divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 151 publications
3
80
0
2
Order By: Relevance
“…Although thousands of lncRNAs have been discovered to date, very little is known about their mode of action and possible role in the regulation of cancer-related processes. The positive correlation of bidirectional sense/antisense transcription is in accord with numerous studies showing that antisense RNAs can regulate their neighboring genes in a cis - mode (Kunej et al, 2014). Here we have shown that although HIF1A-AS2 expression responds to hypoxic stress, it had no effect on the expression of its neighboring gene in sense orientation – HIF1A.…”
Section: Discussionsupporting
confidence: 86%
“…Although thousands of lncRNAs have been discovered to date, very little is known about their mode of action and possible role in the regulation of cancer-related processes. The positive correlation of bidirectional sense/antisense transcription is in accord with numerous studies showing that antisense RNAs can regulate their neighboring genes in a cis - mode (Kunej et al, 2014). Here we have shown that although HIF1A-AS2 expression responds to hypoxic stress, it had no effect on the expression of its neighboring gene in sense orientation – HIF1A.…”
Section: Discussionsupporting
confidence: 86%
“…Mounting evidence shows that lncRNAs play important roles in a large range of biological processes and diseases, especially in cancer biology [9]. Compared with protein biomarkers expressed in multiple tissue types, lncRNAs often exhibit a tissue-specific expression pattern and can be detected easily in body fluids due to high stability, making them ideal biomarkers [10]. Some lncRNAs, such as HOTAIR [11, 12], H19 [2, 13], GAPLINC [14], ANRIL [15], are reported to be oncogenic molecules in GC.…”
Section: Introductionmentioning
confidence: 99%
“…lncRNA is the functional end-product, and the level of lncRNA expression correlates directly with the level of the active molecule. Thus, the use of lncRNAs in diagnostics has intrinsic advantages over the use of protein-coding RNAs (4). In addition, lncRNAs show greater tissue specificity compared to miRNAs and protein-coding mRNAs, making them attractive in the search for novel diagnostic and prognostic cancer biomarkers (5).…”
Section: Introductionmentioning
confidence: 99%